Dampak Pengembangan Pariwisata Terhadap Kondisi Ekonomi Masyarakat - Agnesia Berlina Oktaviani; Eppy Yuliani (Universitas Islam Sultan Agung, 2023)
Tourism is an activity that has a significant influence or change in both positive and negative terms on the environment. Along with the development of the era, the entire tourism sector experienced a development as a form of effort in the development process. However, in general, development activities in the tourism sector can provide good prospects for community economic growth because tourism will create jobs and increase the income of the surrounding community. This study aims to determine how the influence of the development of the tourism sector on the economic situation of the community in several regions spread across Indonesia. This study uses a qualitative method, namely by analyzing several studies on the influence of tourism development on the economic condition of the community which is contained in various journals and scientific works. The focus of writing this article is the impact or changes in the economic conditions of the community from tourism development from previous economic conditions. This research will study the impact of tourism development on the community in 3 tourist sites in Indonesia. The results of this research will show that the development of the tourism sector will have a major impact on society, especially on the economy.Keywords: Tourism, Development, Economy